Language Politeness in Tere Liye's Novel “Leaves That Feel Never Hate the Wind” Deixis Study - M. Joharis Lubis; Fitri Noviyanti Nasution (LingLit Journal Scientific Journal for Linguistics and Literature, 2021)
The purpose of this study was to determine the politeness of language in Tere Liye's novel "The Fallen Leaf Never Hates the Wind" with a deixis study. This research method uses the approach qualitative. The data source of this research is Tere Liye's novel "The Fallen Leaves Don't Hate the Wind". The data collection technique in this study is a literature study technique or literature study. Data collection with this library technique is done by reading, taking notes, studying, and collecting data from written sources. The results of this study were found by using person deixis, time deixis, and place deixis. There are nine person deixis found in the novel, there are seven time deixis determined in the novel, and there is one place deixis found. Persona deixis users dominate in Tere Liye's novels Leaves That Never Fall Hate the Wind.